2020
DOI: 10.1111/ejss.12942
|View full text |Cite
|
Sign up to set email alerts
|

Grassland management effects on earthworm communities under ambient and future climatic conditions

Abstract: The impacts of climate change on biodiversity can be modulated by other changing environmental conditions (e.g. induced by land‐use change). The potential interactive effects of climate change and land use have rarely been studied for soil organisms. To test the effects of changing climatic conditions and land use on soil invertebrates, we examined earthworm communities across different seasons in different grassland‐use types (intensively managed grassland, extensively managed meadow and extensively managed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 57 publications
1
16
0
1
Order By: Relevance
“…The input of organic manures and nonconventional farming system also improves soil quality which promotes earthworm presence within the soil [21,25]. Singh et al [26] also reported that the use of sheep dung in the intensive grassland management increase the earthworm population and their abundance and number increase up to four times which directly affected the earthworm diversity indices [27]. The present study also reported that agricultural management practices such as ploughing, tillage etc.…”
Section: Soil Variables and Earthworm Abundancesupporting
confidence: 57%
“…The input of organic manures and nonconventional farming system also improves soil quality which promotes earthworm presence within the soil [21,25]. Singh et al [26] also reported that the use of sheep dung in the intensive grassland management increase the earthworm population and their abundance and number increase up to four times which directly affected the earthworm diversity indices [27]. The present study also reported that agricultural management practices such as ploughing, tillage etc.…”
Section: Soil Variables and Earthworm Abundancesupporting
confidence: 57%
“…Moreover, the quality of this organic matter showed the lowest alkyl-C/O-N-alkyl-C ratio and C: N ratio (Table 2) than in Graswang and Esterberg. Singh et al (2020) showed as in temperate grasslands the earthworms preferred plant residues with low C: N ratio.…”
Section: Ecological Earthworm Groupsmentioning
confidence: 92%
“…The passage of soil and organic matter through the earthworm gut creates casts formed from differently sized aggregates (Angst et al 2017). Most of the studies about the role of earthworms for C sequestration through aggregation were carried out in agricultural soils (Bossuyt et al 2005;Pulleman et al 2005) and forest soils (Lubbers et al 2013;Zhang et al 2013), but has rarely been studied in grassland soils (Singh et al 2020;Wu et al 2017), despite as compared to other habitats in temperate ecosystems, earthworms are generally more abundant and diverse in grasslands (Keith et al 2018;Spurgeon et al 2013;Singh et al 2020) . Concerning the role of earthworms in soil aggregation, an important information is not only their quantity but also their ecological niche classification, which is based on their feeding guilds, commonly named epigeic, endogeic, and anecic (Bouché 1977;Shipitalo and Le Bayon 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Besides determination of abundance, body masses were also estimated for springtails, mites and earthworms as intensive management practices may select for soil arthropod communities with particular life history traits ( Birkhofer et al, 2017 ), such as small body size, and may decrease earthworm biomass ( Singh et al, 2021 ). The body length of each springtail was measured under a microscope and, for each sample (four samples per plot), the mean body length of each collembolan sub-family was estimated.…”
Section: Methodsmentioning
confidence: 99%